Nkanelo wa nkoka wa vuhundzuluxi eka tsalwa ra xitlhangu ra G. S. Mayevu: maendlelo ya vuhundzuluxi bya ntumbuluko - Ntimbana, M. H. (University of Limpopo, 2014)
This topic outlined the importance of translation of Xitsonga novel which is translated in Xitsonga by G.S. Mayevu. This showed how translation is so important in Xitsonga language. Mayevu and other translators had tried their level best to better the Xitsonga language through translation. This research pointed out in details problems which translators come across and how these problems can be overcomed. In this research, we also realised how scarce students who are doing translation are. The researcher also recommend that translation be taken into consideration in the world at large because people can together, discuss and agree on issues through translation.
Thesis (M. A. ( Translation Studies)) --University of Limpopo, 2014
Keywords: Translation; Biographical fiction; Tsonga literature -- Translations